Criterion validity of the Ekblom-Bak and the Åstrand submaximal test in an elderly population - Väisänen, Daniel (Eur J Appl Physiol, 2019)
PURPOSE: The aim of this study was to validate the submaximal Ekblom-Bak test (EB-test) and the Åstrand test (Å-test) for an elderly population. METHODS: Participants (n = 104), aged 65–75 years, completed a submaximal aerobic test on a cycle ergometer followed by an individually adjusted indirect calorimetry VO(2)max test on a treadmill. The HR from the submaximal test was used to estimate VO(2)max using both the EB-test and Å-test equations. RESULTS: The correlation between measured and estimated VO(2)max using the EB method and Å method in women was r = 0.64 and r = 0.58, respectively and in men r = 0.44 and r = 0.44, respectively. In women, the mean difference between estimated and measured VO(2)max was − 0.02 L min(−1) (95% CI − 0.08 to 0.04) for the EB method and − 0.12 L min(−1) (95% CI − 0.22 to − 0.02) for the Å method. Corresponding values for men were 0.05 L min(−1) (95% CI − 0.04 to 0.14) and − 0.28 L min(−1) (95% CI − 0.42 to − 0.14), respectively. However, the EB method was found to overestimate VO(2)max in men with low fitness and the Å method was found to underestimate VO(2)max in both women and men. For women, the coefficient of variance was 11.1%, when using the EB method and 19.8% when using the Å method. Corresponding values for men were 11.6% and 18.9%, respectively. CONCLUSION: The submaximal EB-test is valid for estimating VO(2)max in elderly women, but not in all elderly men. The Å-test is not valid for estimating VO(2)max in the elderly. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00421-019-04275-7) contains supplementary material, which is available to authorized users.